Perencanaan Tempat Wudhu Masjid Iqomatuddin - Adeswastoto, Hanantatur; Putra, Agus Alisa; Fitri, Normelia; Amanda, Putri; Mardani, Bisma Alfian (Journal of Social and Community Service, 2023)
The Iqomatuddin Mosque in Pulau Terap Village, Kuok District, has experienced an increase in the number of worshipers in line with development developments around it. However, the current toilet and ablution facilities are considered inadequate, causing long queues and inconvenience for the community, especially during congregational prayers. Based on a preliminary survey by the Civil Engineering Study Program community service team, it was agreed to convert the Madrasah Diniyah Awaliyah (MDA) classrooms, which are currently less active, into additional facilities in the form of toilets and ablution areas. This service activity includes two main stages, namely design planning and preparation of a budget plan (RAB) of Rp. 4,800,000. This program also includes outreach and training for local communities to support its smooth implementation.